The Eucharist as a sacrament of unity. The legal consequences of Church Magisterium in accordance to regulations included in Codex Canonum Ecclesiarum Orientalium - HOŁUBOWICZ, RAFAŁ (Prawo Kanoniczne, 2014)
In the first words of his last encyclical Ecclesia de Eucharistia, blessed John Paul II reminded what have been determining the foundation of Church teaching, from the very beginning: «The Church lives thanks to Eucharist. That truth not only expresses the everyday faith experience but also contains the essence of Church mystery. The Church feels with great joy and in immense variety of ways, that the promise: “And now I am with You, through all these days, until the world ends” (Mt 28, 20) is continually coming true. Thanks to Sacred Eucharist, during which wine and water are being transformed to Holy Blood and Body of Jesus Christ, the Church rejoices in this presence in a unique way. In this meaning, The Eucharist, that is always in the center of Christian’s life, becomes for whole community of believers, in particular way, the sacrament of unity. The last Council reminded this fact, telling that the sacrament of Eucharist, constituted by Jesus Christ during the Last Supper, which not only reminds but also embodies in a real way the Sacrifice of the Cross is, first of all, the sacrament of God’s mercy, sign of unity, love tie and paschal feast. It is necessary to underline the fact that according to council’s teaching, Eucharist is not only the sign of whole Church community, but also the sacrament, which really builds and strengthens the unity of all Christians. The teaching of council fathers determines the base of present canonical legislation within whole Catholic Church, both Latin and East. Though canon number 698 reads: «In God’s liturgy, through the service of the Christ impersonated by the priest, celebrated over the Church gifts, by the power of Holy Spirit, continuously there is performed exactly the same what Jesus himself made during the Last Supper, when he gave to his Apostles his body sacrificed on the cross for our redemption and also his blood, shed for our sins, constituting the real and mystic sacrifice in which sacrifice of the cross is being recalled with thanksgiving, presented, and in which the Church takes part through the contribution and communion for expressing and improving the unity of God’s People, to build his own Body, which means the Church». Consequences of this canon, with strong theological sound, occur in next canons concerning the sacrament of Eucharist. There is possible to find inside them norms regarding to active participation of worshippers in celebration of the Eucharist, which causes that the internal unity of God’s People gathered around Christ’s Altar, becomes expressed also in external form as well as the norm regarding to an individual celebration of God’s Liturgy or concelebration made by many priests. The problem of concelebrating is extremely important due to the fact, that just in this form of celebrating the God’s Liturgy, there is visible its uniting function. The base to define which form (individual or concelebrated one) is advisable in particular situation, is pastoral criterion. Priestly favors allow even to concelebrate the Eucharist by bishops and priests belonging to different Churches sui iuris, every time when justified reason exists, and there is no danger of liturgical syncretism; rules of liturgical books that belong to main celebrant are kept and colours of canonicals are used according to own Church rules. These and other norms enclosed in Codex Canonum Ecclesiarum Orientalium, pointing out in a perfect way the Eucharist as a sacrament of unity for everyone who have been baptized, constitute canonical translation of the theological teaching that have been given by Second Vatican Council and regulate presently all of the liturgical life of east Catholics.